IMPORTANT ASPECTS OF THE STUDY OF PAROEMIAS IN ENGLISH AND UZBEK TEXTS (Scientific journal of the Fergana State University, 2024)
In this article, based on the analysis of the issues of linguistic and cultural research of the paremias observed in texts in foreign languages, in particular English and Uzbek, the main goal of linguistic and cultural studies is formulated -the study of language and culture and stereotypes highlights the role of culture, its content, and the factors influencing its specifics.